Strength Training for Stroke Recovery: What are its effects, how to prescribe it, and who is engaging in it? - Noguchi, Kenneth S (My University, 2024)
People with stroke may experience losses of muscle strength and physical function. The two are related, whereby a threshold of strength is often needed to execute activities of daily living. Strength training (ST) is a potent stimulus to elicit gains in muscle mass, strength, and function. However, it is underutilized in clinical practice due to ambiguity around how to prescribe it. It is also unclear to which extent people with stroke are currently engaging in these activities. The purpose of this thesis was to advance the understanding and application of ST in stroke rehabilitation. Study 1 was a systematic review and meta-analysis of 39 trials (n=1,928), which found that ST improved both muscle strength, as well as outcomes rated as important by a community advisory group of adults with stroke, such as balance, walking capacity and speed. We also found that traditional ST programs using free weights and machines, power-focused intensities (i.e., exercises performed at lower external resistance and high speeds), and more frequent ST were more beneficial for some aspects of stroke recovery. Study 2 examined the feasibility and effects of a 10-week power-focused ST program on muscle strength, power, physical function, and health-related quality of life in 15 people living with mild to moderate chronic stroke. We found that the study was feasible with respect to participant recruitment, sex and gender distribution, attendance, attrition, safety, exercise tolerance, and satisfaction with the program. Moreover, the program showed potential for clinically important improvements in physical function and health-related quality of life. Finally, Study 3, was a cross-sectional study (n=2,094) using data from the Canadian Longitudinal Study on Aging which found that fewer than a quarter of Canadians with stroke engage in muscle strengthening activities and are not likely to meet moderate to vigorous physical activity (MVPA) guidelines. Moreover, people with lower intrinsic capacity, functional mobility, and negative environments had lower physical activity levels. These findings suggest that ST is effective and may be feasibly optimized through power-focused intensities. However, very few people with stroke reported engaging in ST, indicating that health promotion should be a key focus for future research and practice.
Strength Training for Stroke Recovery: The What, How, and Who?
Keywords: Stroke; Exercise therapy; Rehabilitation; Neurology